Cyanobacteria isolated from the high-intertidal zone: a model for studying the physiological prerequisites for survival in low Earth orbit. Issue 4 (29th May 2013) - Olsson-Francis, Karen; Watson, Jonathan S.; Cockell, Charles S.
Abstract: Cyanobacteria are capable of surviving the adverse conditions of low Earth orbit (LEO). We have previously demonstrated that Gloeocapsa strain OU_20, Chroococcidiopsis and akinetes of Anabaena cylindrica were able to survive 548 days of exposure to LEO. Motivated by an interest to understand how cyanobacteria can survive in LEO, we studied the strategies that Gloeocapsa strain OU_20 employs to survive in its natural environment, the upper region of the intertidal zone. Here, cyanobacteria are exposed to fluctuations in temperature, UV radiation, desiccation and salinity. We demonstrated that an increase in salinity from 6.5‰ (BG-11 medium) to 35.7‰ (similar to that of seawater), resulted in increased resistance to UV radiation (254 nm), vacuum (0.7×10 −3 ±0.01 kPa) and cold temperatures (–20 °C). Concomitantly, biochemical analyses demonstrated that the amount of fatty acids and mycosporine-like amino acids (a UV absorbing pigment) were higher in the stressed cells. Morphological analysis demonstrated that the electron density and thickness of the mucilaginous sheath were also greater than in the control cells. Yet, the control and stressed cells both formed aggregates. As a result of studying the physiological adaptation of Gloeocapsa strain OU_20 in response to salinity, we postulate that survival in the high-intertidal zone and LEO involves a dense extracellular mucilaginous sheath and the formation of aggregates. We conclude that studying the physiological adaptation of cyanobacteria in the intertidal zone provides insight into understanding survival in LEO.